-6w-2(-3x+6w)+2x=

Simple and best practice solution for -6w-2(-3x+6w)+2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6w-2(-3x+6w)+2x= equation:


Simplifying
-6w + -2(-3x + 6w) + 2x = 0

Reorder the terms:
-6w + -2(6w + -3x) + 2x = 0
-6w + (6w * -2 + -3x * -2) + 2x = 0
-6w + (-12w + 6x) + 2x = 0

Combine like terms: -6w + -12w = -18w
-18w + 6x + 2x = 0

Combine like terms: 6x + 2x = 8x
-18w + 8x = 0

Solving
-18w + 8x = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-18w + 8x + -8x = 0 + -8x

Combine like terms: 8x + -8x = 0
-18w + 0 = 0 + -8x
-18w = 0 + -8x
Remove the zero:
-18w = -8x

Divide each side by '-18'.
w = 0.4444444444x

Simplifying
w = 0.4444444444x

See similar equations:

| 8x(-7)+8-(-10)= | | 7=-16x^2+24x+1 | | 1.5=10*1 | | 15(-21x+20)=15(-4x+122) | | 2x-3=8x-33 | | 6.2x+6.6-3.4x=20.6 | | 23=3x | | -17=3x-8 | | -5x+46=5+9(8x-4) | | a^3-1698a-2704=0 | | -4x-10=11 | | 1m+10=80 | | 33-x=222 | | 3(9x+7)=27x-1 | | 5(3-2x)=10(4-2x)-85 | | 4(x-10)=5x-45 | | 2x-5x-2=-3+4x-43 | | y=-1+-0.1666666667x | | IV=ir | | a^4-1698a-2704=0 | | 88-6x=-10x+85 | | -46-8x=5(-7x+7) | | 3=5-2 | | 75+10=15h | | 2(1.5)-3y=2 | | 4u-6=-2 | | p-0.30p=25.20 | | -20=4w | | 8x+6x-20=60-6x | | 7x+4q=8+3q | | 2(y)+8=8 | | y=x^3-6x^2-36x+15 |

Equations solver categories